Strain and curvature‐independent temperature sensor based on an interferometer taper fabricated with a CO2 laser. Issue 3 (March 2016) - Martins, T. J. M.; Marques, M. B.; Frazão, O.
ABSTRACT: An optical fiber interferometer taper fabricated with a CO2 laser is proposed for strain and curvature‐independent temperature measurement. Variations in temperature produce changes in the conditions of the interference between light traveling along the core and cladding and a linear behavior is verified for the relation between the wavelength of the resonant loss peak and temperature, yielding a sensitivity of 110 pm/°C for a range between 25 and 510°C. Both the applied strain and curvature only promote significant changes in the transmitted power, leaving the wavelength of the resonant loss peak approximately constant and rendering this optical sensing device a good strain and curvature‐independent temperature sensor. © 2016 Wiley Periodicals, Inc. Microwave Opt Technol Lett 58:688–691, 2016